2005
DOI: 10.1038/emm.2005.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of CYP17 and breast cancer risk in Korean women

Abstract: A bstractC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The polymorphisms were detected using a modified PCR-RFLP method [14,15]. The PCR primers were synthesized by TAG Copenhagen A/S.…”
Section: Genotypingmentioning
confidence: 99%
“…The polymorphisms were detected using a modified PCR-RFLP method [14,15]. The PCR primers were synthesized by TAG Copenhagen A/S.…”
Section: Genotypingmentioning
confidence: 99%
“…Three previous systematic reviews (in 1999 [33] and in 2002 [34,35]) concluded that risk was not significantly or weakly associated with CYP17 T34C polymorphism. Nevertheless, more recent case-control studies showed that an increased occurrence of breast cancer in carriers of C allele [24,25,27,29,32].…”
Section: Introductionmentioning
confidence: 96%
“…Due to individual differences in exposure to factors modifying genetic levels of E 2 , however, a relationship between CYP17 genetic polymorphism and risk of breast cancer may not be detectable. Several studies tested the relationship between CYP17 polymorphism and risk of breast cancer (23,37,42,(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), but results are conflicting.…”
Section: Discussionmentioning
confidence: 99%